Granules hydroxyapatite application in fractures - Zulkifly, Ahmad Hafiz; Khalid, Kamarul Ariffin; Mohd Amin, Azril; Awang, Mohd Shukrimi; Mohd Yusuf, Nazri; Che Ahmad, Aminudin; Zakaria@Mohamad, Zamzuri; Fazan, Fazilah (AO Research Institute Davos, 2008)
In conjunction with a multi-institution research project, towards achieving the production of a locally made bone graft substitute. Hydroxyapatite (HA) granules made from local raw materials have been fabricated using a novel method (Patent (Pending) No. PI 2004 0748). The granules were characterised both chemically and physically and found to abide by the ASTM F1185 - 88 (1993) specification that covers the material requirements for HA intended for use as surgical implants. A phase 1 clinical trial involving the use of the granules for root socket obliteration in young healthy adults following tooth extraction was performed. Based on the results of these studies, the material was approved for a phase 2 clinical trial. The study was approved by the University and Hospital Clinical Ethical Committee in July 2005